MATHEMATICAL MODEL OF THE MALE URINARY TRACT - Kren, Jiri; Horak, Miroslav; Zatura, Frantisek; Rosenberg, Mita (Biomedical papers, 2001)
The paper presents a simplified (but not trivial) mathematical model of the interaction between the urine flowand the male urethra and bladder, respectively. Urine is assumed to be a Newtonian fluid. The flow is considered tobe non-stationary, isothermal and turbulent. The urethra and bladder wall, featuring elastic properties, experiencelarge displacements and strains. The dynamic forces are included in the urethra wall motion. When fully extendedthe urethra attains the shape of an axisymetric tube. An iterative method based on the uncoupled approach isdeveloped.
Keywords: Keywords: Interaction / Uncoupled method / Non-linear continuum / Equation of motion / FEM